Devenir reine kakataibo. Performance, séduction et genre en Amazonie péruvienne - Magda Helena Dziubinska (Journal de la Société des Américanistes)
Through an ethnography of beauty contests organized in a Kakataibo Native Community (Peruvian Amazon), this article examines on the one hand the young Kakataibo women’s experience of femininity, and on the other hand, the relations of Kakataibo with the non-indigenous population of the region. In contrast to the beauty contests organized in other indigenous contexts which expose and affirm cultural difference or ethnicity, the Kakataibo version aims to stage the figure of the white woman transformed into an object of desire. This performance can be understood through the transformations that are taking place in Amerindian villages, and related closely to education, modes of gender construction and more generally to the new politics of the body. Privileging a pragmatic and interactionist approach, we initially focus on the spectacular and mimetic aspects of the event (training, costumes, choreography), and then proceed to examine the performative dimension of this specific play of being the Other.